Character Education Management for Students at SMP Muhammadiyah 2 Bandung - Sulastri, Neneng; Kumar, Saurav (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study aims to 1) describe and analyze the planning of character education at SMP Muhammadiyah 2 Bandung, 2) describe and analyze the implementation of character education at SMP Muhammadiyah 2 Bandung, and 3) describe and analyze the evaluation of character education at SMP Muhammadiyah 2 Bandung. A case study research method was used with a qualitative approach. Data collection techniques included interviews, observations, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was ensured through persistent observation and triangulation. The findings reveal that the management functions applied at SMP Muhammadiyah 2 Bandung include: (1) Planning for character education by determining the character values to be developed, preparing teaching and administrative staff, reviewing documents related to the implementation of character education reinforcement, and socializing policies to the entire school community, students' parents, and the related public; (2) Implementation of character education by integrating the formulated character education content into all subjects as well as into programmed or planned activities; incorporating character education into daily activities at the school through habituation and role modeling; and fostering communication and collaboration between the school and students' parents; (3) Evaluation of character education is conducted through program evaluation, process evaluation, and outcome evaluation.